The extraordinary adventures of foundling Mick - Verne, Jules, 1828-1905 (The Irish novel, 2008)
A story of a young orphan's trials and tribulations in the late nineteenth century. It provides description of and commentary on contemporary Ireland. It takes readers on a tour of Ireland and her social classes. It also shows the Frenchman's affection and respect for Ireland and her people.